Peran Bank Wakaf Mikro dalam Pemberdayaan Ekonomi Masyarakat - Fathoni, Ahmad Fauzan; Faidati, Nur (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The purpose of this research is to explain the role of BWM UNISA in empowering the community's economy. The research method used in this research is descriptive qualitative which explains the phenomenon in depth through data collection including observation, interviews and documentation. The data analysis techniques used are reduction, data display, and conclusion darwing or verification. The results showed that the UNISA Micro Waqf Bank (BWM) proved to be an important solution in poverty alleviation and economic empowerment of the lower middle class. BWM Unisa provides financing (qardh contract) and mentoring (HALMI) on a regular basis. The assistance provided by BWM is beneficial for customers in improving their capabilities, managing finances, capital, profits, and marketing insights.